Effects of the Incubation Period of Pleurotus ostreatus on the Chemical Composition and Nutrient Availability of Solid-State-Fermented Corn Stover - Lydia K. Olagunju; Omoanghe S. Isikhuemhen; Peter A. Dele; Felicia N. Anike; Kelechi A. Ike; Yasmine Shaw; Rosetta M. Brice; Oluteru E. Orimaye; Michael Wuaku; Brandon G. Essick; Nathan Holt; Nkese S. Udombang; et al. (Animals, 2023)
The current study aimed to optimize and improve the feeding value of Pleurotus ostreatus-fermented corn stover by evaluating the effects of five solid-state fermentation times and three in vitro fermentation periods on the chemical composition, dry matter disappearance (DMD), microbial mass and volatile fatty acid (VFA) production of treated and untreated corn stover. The study utilized a 3 × 5 factorial design, with eight replicates per treatment. Dry matter, crude protein (CP), ash and non-fiber carbohydrate (NFC) contents increased quadratically (p < 0.05) with increases in the solid-state fermentation time. Increases of 44.4–59.1%, 20.6–78.6% and 40.5–121% were noted for the CP, ash and NFC contents, respectively. Organic matter, ether extract, neutral detergent fiber and hemicellulose contents decreased quadratically (p < 0.05) across the treatments. Similar trends were noted for DM and fiber disappearance in the treatments. The total gas production and in vitro true dry matter digestibility (IVTDMD) increased quadratically, while microbial mass and in vitro apparent DMD increased in a linear manner. The total VFA, propionate and butyrate contents increased linearly. Both the acetate content and the A:P ratio decreased in a linear manner. The results show that the rumen fermentation pathway favors the production of propionate, with increases in propionate production of 7.46 and 8.30% after 2 and 4 wk, respectively. The study showed that a 2 wk period of solid-state fermentation is sufficient to provide a bio-transformed cow–calf feed resource from P. ostreatus-treated corn stover.